Analysis oflmpact ofTelevision Advertising on Children - Singh, Sultan; Kaur, Jaiman Preet (Gyan Management Journal, 2011)
Television viewers, these days, are bombarded with increasing commercial content. From the barrage of 15-second commercial, to product placement or to infomercials, when the viewer watches television, they are constantly exposed to some form of advertising. Over the past two decades, seminal work on the effect of the advertisements on children,family buying decisions and consumer behaviour has been overlooked. Today’s children can recognize hundreds of brand names and logos. The purpose of this study is to deliberate upon TV advertising and its impact on children. This paper highlights and investigates the influence that children have on family buying behaviour such as unnecessary purchases, eating disorders and behavioural changes. A questionnaire using five-point likert scale was administered to 150 parents of children aged between 3-15 years. Samples were drawn through random and convenience sampling approach from cities of Haryana namely Sirsa, Hisar; Panipat, Karna/ and Sonepat. Data were analyzed by using SPSS software. Statistical tools such as Cross-tables, Factor-analysis test, Chi-square test and One-way AN OVA are used for analyzing the data. This paper takes the unique approach of investigating purchase influence from the perspective of both the child and the parent. High and low involvement products have been considered, along with children’s age, parents’ income and a variety of demographic factors.